The Biochemistry of plants : a comprehensive treatise - Stumpf, Paul K. (Paul Karl), 1919-2007; Conn, Eric E.; Miflin, B. J.; Lea, Peter J.
This volume covers the most significant advances of the last ten years in understanding intermediary nitrogen metabolism in plants. The eight chapters comprise aspects of nitrate and nitrogen assimilation, symbiotic nitrogen fixation, glutamine and glutamate enzymology, amino acid biosynthesis, ureides, and polyamine and sulfur metabolism. The volume emphasizes molecular and genetic advances as well as biochemistry and physiology. Intermediary Nitrogen Metabolism will be of interest to all plant biochemists and molecular geneticists who study nitrogen metabolism, enzymology, and amino acids.